PENGARUH UKURAN DEWAN DIREKSI, UKURAN KOMITE AUDIT DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN ENVIRONMENTAL SOCIAL AND GOVERNANCE (ESG) (Studi pada Perusahaan Non-keuangan yang Terdaftar di BEI pada Tahun 2021-2023) - Muhammad Nabiel Aulia Azmi; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of board size, audit committee size and company characteristics on Environmental, Social, and Governance (ESG) Disclosure. The independent variables in this study include board size, audit committee size, firm size, and firm age, while the dependent variable is ESG disclosure. The population of this study consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sample was selected using the purposive sampling method, resulting in 363 samples. The analysis was conducted using multiple linear regression with the help of IBM SPSS 26.0. The results indicate that board size, firm size, and firm age have a positive and significant effect on ESG disclosure. On the other hand, audit committee insignificant effect on ESG disclosure.